Training Management in Enhancing the Professionalism of English Teachers - Reny Tri Susanti; Albert Efendi Pohan; Tubagus Pamungkas (JURNAL INOVASI PENDIDIKAN DAN SAINS, 2026)
This study aims to analyze the management of training in enhancing the professionalism of English teachers at Sekolah Menengah Kejuruan (SMK) Kota Batam, focusing on planning, implementation, and evaluation, as well as its effectiveness in improving teachers’ competencies. A mixed methods approach with an explanatory sequential design was employed. The quantitative phase involved a survey of 35 English teachers at SMK Kota Batam using a validated Likert-scale questionnaire, analyzed through multiple linear regression. The qualitative phase was conducted through limited written interviews to explain and strengthen the quantitative findings. The results show that training management has a significant positive effect on improving teachers’ professionalism. Effective planning, structured implementation, and comprehensive evaluation contribute to the development of teachers’ pedagogical, professional, and technological competencies. Furthermore, well-managed training programs support the creation of systematic, targeted, and sustainable professional development for English teachers at SMK Kota Batam